MicroRNA-33b is a Potential Non-Invasive Biomarker for Response to Atorvastatin Treatment in Chilean Subjects With Hypercholesterolemia: A Pilot Study - Ubilla, Carmen Gloria; Prado, Yalena; Angulo, Jeremy; Obreque, Ignacio; Paez, Isis; Saavedra, Nicolás; Saavedra, Kathleen; Zambrano, Tomás; Salazar, Luis A. (Frontiers in Pharmacology, 2021)
Evidence accumulated so far indicates that circulating levels of microRNAs (miRNAs) are associated with several pathologies. Therefore, differential expression of miRNAs exhibits promising potential for screening and diagnosis purposes. We evaluated the effect of the lipid-lowering drug atorvastatin on circulating miRNAs in patients with hypercholesterolemia and controls. Methods: Ten microRNAs (miRNA-17-5p, miRNA-30c-5p, miRNA-24-3p, miRNA-33a-5p, miRNA-33b-5p, miRNA-29a-3p, miRNA-29b-3p, miRNA-454-3p, miRNA-590-3p and miRNA-27a-3p) were assessed in 20 hypercholesterolemic (HC) patients before and after 1 month of 20 mg/day atorvastatin treatment. The same miRNA set was additionally determined in a group of 20 healthy subjects showing a normal lipid profile (NL). We employed bioinformatics tools (miRBase, miRTargetLink Human, GeneCards, and Pharmaco miR) to identify miRNAs associated with cholesterol metabolism and statin response genes. The expression of miRNAs was determined by qRT-PCR using TaqMan assays. Results: Hypercholesterolemic individuals showed significant overexpression of miRNA-30c-5p and miRNA-29b-3p vs. normal subjects (p=0.0008 and p=0.0001, respectively). Once cholesterol-lowering treatment was concluded, HC individuals had a substantial increase of three extracellular miRNAs (miRNA-24-3p, miRNA-590, and miRNA-33b-5p), the latter elevated more than 37-fold (p=0.0082). Conclusion: Data suggest that circulating miRNA-30c-5p and miRNA-29b-3p are associated with hypercholesterolemia. Also, atorvastatin induces a strong elevation of miRNA-33b-5p levels in hypercholesterolemic individuals, which could indicate an important function this miRNA may exert upon atorvastatin therapy. Nonetheless, additional studies are needed to clarify this particular miRNA's role in statin treatment.